REVIEW: THE EFFECT OF VARIOUS COMBINATIONS OF GROWTH REGULATORY SUBSTANCES (ZPT) IN EMBRYOGENIC CALLUS INDUCTION - Andrea, Vincent (Journal Pharmacy Of Tanjungpura, 2024)
Callus induction is the early stage of an outside systemic culture method which purpose to make and multiply callus cells en masse. Callus is a very important source of plant material in plant regeneration because every plant cell has the capability to form new singles. This review article is an effort to develop studies in plant cell and tissue culture technology, namely callus induction of plant regeneration responses in vitro. The method used is to conduct an online search using GoogleChrome on the Google Scholar site with the keywords "Tissue Culture", " Biotechnology", "Callus Induction", and "Regeneration". The sources obtained were national journals selected based on inclusion criteria, namely journals published in the last 10 years with research articles or original articles with correlations or similarities in the content of the articles. The research results show that 2,4-D is an auxin or growth regulator which is always used in embryogenic callus induction. The use of this powerful auxin can be combined with several other growth regulators such as NAA, IBA, kinetin, and BAP.